Coupling adaptation mode and regulation strategy for the wind–thermal climate environment of vernacular dwellings in Jiangnan, China based on regional bioclimatic evaluation - Tianyi Min; Tong Zhang (Journal of Asian Architecture and Building Engineering)
With the increasing reliance on mechanical devices and the diminishing connection with climate and region, architecture is falling into a paradigm of “isolation” from the environment. As native building types, vernacular dwellings present the mode of human – environment mutualism, which is an important reference for responding to low-carbon and sustainable development of buildings and reshaping regional architectural styles. This study choses vernacular dwellings in Jiangnan, China as the research objects, focusing on the wind – thermal climate environment coupling adaptation mode and regulation strategy under the hot-summer and cold-winter zone. First, by using bioclimatology methods, the theoretical range of passive climate control zones in Jiangnan area during the summer and winter seasons was anatomically analyzed with the actual range of passive climate conrrtrol zones of Jiangnan dwellings. Second, the wind-thermal climate adaptation mechanism was comprehensively interpreted from climatological situation, space configuring type, climate space gradient and climate regulation interface four perspectives. Finally, from the perspective wind – thermal environments are respectively synergistic and contradictory in summer and winter, the coupling adaptation mode and strategy of Jiangnan residential climate adaptation are proposed, as well as a passive building regulation paradigm for hot-summer and cold-winter climate type, which provides an important way to promote climate-responsive sustainable development.